If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 44 + -3x = 15x + 16 Reorder the terms: 44 + -3x = 16 + 15x Solving 44 + -3x = 16 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 44 + -3x + -15x = 16 + 15x + -15x Combine like terms: -3x + -15x = -18x 44 + -18x = 16 + 15x + -15x Combine like terms: 15x + -15x = 0 44 + -18x = 16 + 0 44 + -18x = 16 Add '-44' to each side of the equation. 44 + -44 + -18x = 16 + -44 Combine like terms: 44 + -44 = 0 0 + -18x = 16 + -44 -18x = 16 + -44 Combine like terms: 16 + -44 = -28 -18x = -28 Divide each side by '-18'. x = 1.555555556 Simplifying x = 1.555555556
| 2(5-4)= | | (2-5)= | | 7*-2+3= | | 0.08x+0.07(15000-x)=1110 | | 2k+h=1 | | -3x-4(-0.5+-0.75)=2 | | 5*3+4= | | -32+9x=8+5x | | X-8=2x+9 | | -2x^3(3x^2-6x-1)= | | -7z-49=2-6z | | -3(-2.6-1)+5=2(-2.6+1)-3(-13-1)+13 | | -29+x=-7x+51 | | h+2k=14k | | 3.4x-4.6=2.2 | | -46+2x=30+6x | | 12k=1-2k | | 6m-5=7m+5-m | | 19-h-h=-18 | | 7-(9x+3)=-9x-4 | | x(7+66)= | | y=2-5+-2.5 | | 7-x+4=27 | | x^8-24x^4+128=0 | | 4x*2+9x+22=0 | | 75=(3-6n-5) | | 7-4x=-1 | | 2+-1=5+-2.5 | | x+2x+6x+1=46 | | 7z+6=-7-5 | | 6n^2= | | 3y+7=3 |